Coupled Evolution of Deformation, Pore Fluid Pressure, and Fluid Flow in Shallow Subduction Forearcs. Issue 3 (21st March 2020) - Sun, Tianhaozhe; Ellis, Susan; Saffer, Demian
Abstract: Deformation and fluid flow in subduction zone forearcs are dynamically coupled, but our quantitative understanding of their coupling is incomplete. In this work, we investigate the hydrological and mechanical coupling in shallow forearcs, using a Lagrangian‐Eulerian finite element model that incorporates constitutive and transport properties of sediments and faults constrained by laboratory and field measurements. Wide‐ranging observations show that sediment thickness and composition, plate convergence rate, basement strength and roughness, and subducting slab dip angle vary between subduction zones. We therefore systematically study their effects on forearc stress and pore fluid pressure states, consolidation and dewatering patterns, and margin morphology. Our models, with the incorporation of a simple description of permeability enhancement along fault damage zones, yield a range of fault permeability (10 −13 –10 −17  m 2 ) consistent with previous estimates and describe the important role of upper plate splay faults in causing heterogeneous dewatering and consolidation patterns and in modulating effective normal stress on the plate interface. Spatial variations in tectonic loading and sediment consolidation can also be caused by subducting basement roughness such as a horst‐and‐graben structure. For typically observed relief and spacing, our models predict locally enhanced porosity reduction by up to 50% at the downdip edge of the horsts and anomalously high sediment porosity above the geometrical highs. At the margin scale, our results demonstrate that sediment permeability and thickness are dominant controls on fluid overpressure, sediment compaction, and megathrust strength. Rough and frictionally strong megathrusts produce similar effects in driving high wedge tapers. Key Points: Coupled deformation and fluid flow govern fault structure, stress, and pore pressure evolution and modulate subduction wedge morphology Drainage along upper plate faults enhances consolidation and locally increases effective normal stress on the megathrust Subducting roughness leads to complex loading and drainage patterns accompanied by heterogeneities in stress and consolidation states